2007
DOI: 10.1111/j.1468-005x.2007.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Telework, human resource flexibility and firm performance

Abstract: The results of a survey of 156 Spanish firms indicate that HR development practices are positively associated to the intensity of telework adoption and they moderate the relationship between telework and firm performance. The positive moderator effect of HR development practices indicates that their implementation is necessary not only to facilitate telework adoption but also to enhance the otherwise marginal contribution of telework at organisational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 75 publications
(88 reference statements)
3
66
0
6
Order By: Relevance
“…In similar circumstances, a case study of British Telecom, well known for its provision of flexible working options (DTI 2005), reported that its use of FWAs resulted in productivity increases of up to 20% (Mahajan and Foggin 2006). Stavrou's (2005) large European study showed that remote working was related to perceptions of improved performance and, in a series of investigations in Spanish firms, Martinez-Sanchez et al (2007a, 2007b found that the use of both remote working and schedule flexibility were positively related to firm performance. In addition to confirming previous findings on remote working, Martinez-Sanchez et al (2008) found that performance was positively associated with intensity of adoption.…”
Section: The Direct Association With Organizational Performancementioning
confidence: 99%
“…In similar circumstances, a case study of British Telecom, well known for its provision of flexible working options (DTI 2005), reported that its use of FWAs resulted in productivity increases of up to 20% (Mahajan and Foggin 2006). Stavrou's (2005) large European study showed that remote working was related to perceptions of improved performance and, in a series of investigations in Spanish firms, Martinez-Sanchez et al (2007a, 2007b found that the use of both remote working and schedule flexibility were positively related to firm performance. In addition to confirming previous findings on remote working, Martinez-Sanchez et al (2008) found that performance was positively associated with intensity of adoption.…”
Section: The Direct Association With Organizational Performancementioning
confidence: 99%
“…A literatura sobre teletrabalho aponta a redução de custos dos escritórios como um dos primeiros objetivos das empresas ao adotarem esse tipo de solução (BENTLEY;YOONG, 2000;MARTÍNEZ-SÁNCHEZ et al, 2007;NILLES, 1996;PATRICKSON, 2002). Segundo Nilles (1996), essa pode ser uma vantagem também para o trabalhador, uma vez que há a tendência deste reduzir seus gastos com deslocamentos e alimentação.…”
Section: Vantagens E Desvantagens Do Teletrabalhounclassified
“…Autores como Martínez-Sánchez et al (2007) e Tremblay (2002) adotam definições mais genéricas para o teletrabalho, como a de que se trata de uma forma de trabalhar mediada pela TIC, em que, pelo menos, parte das atividades é desenvolvida fora do escritório da organização. Outros, como Costa (2004) e Wilks e Billsberry (2007), chamam a atenção para o quanto a simples diferenciação em função do distanciamento do escritório da empresa se mostra limitada para refletir toda a gama de situações que podem ser enquadradas no conceito de teletrabalho.…”
Section: Introductionunclassified
“…Felstead, Jewson, Phizacklea & Walters, 2002;Hill, Ferris & Märtinsson, 2003 ;Kurland & Cooper, 2002 ;Tremblay, 2002), en matière de gestion des connaissances et la performance organisationnelle (voir p.ex. Daniels, Lamond & Standen, 2001 ;Gajendran & Harrison, 2007;Illegems & Verbeke, 2004 ; Martinez-Sanchez, Perez-Perez, de Luis Carnier & Vela- Jimenez, 2007). Document téléchargé depuis www.cairn.info ---203.78.118.211 -02/02/2018 11h09.…”
Section: Frunclassified